Influences of noise reduction on speech intelligibility, listening effort, and sound quality among adults with severe to profound hearing loss - Dong, Ruijuan; Liu, Pengfei; Tian, Xin; Wang, Yuan; Chen, Younuo; Zhang, Jing; Yang, Liu; Zhao, Shiyang; Guan, Jingjing; Wang, Shuo (Frontiers in Neuroscience, 2024)
Introduction: Noise reduction (NR) algorithms have been integrated into modern digital hearing aids to reduce noise annoyance and enhance speech intelligibility. This study aimed to evaluate the influences of a novel hearing aid NR algorithm on individuals with severe-to-profound hearing loss. Methods: Twenty-five participants with severe-to-profound bilateral sensorineural hearing loss underwent three tests (speech intelligibility, listening effort, and subjective sound quality in noise) to investigate the influences of NR. All three tests were performed under three NR strength levels (Off, Moderate, and Strong) for both speech in noise program (SpiN) and speech in loud noise program (SpiLN), comprising six different hearing aid conditions.Results: NR activation significantly reduced listening effort. Subjective sound quality assessments also exhibited benefits of activated NR in terms of noise suppression, listening comfort, satisfaction, and speech clarity.Discussion: Individuals with severe-to-profound hearing loss still experienced advantages from NR technology in both listening effort measure and subjective sound quality assessments. Importantly, these benefits did not adversely affect speech intelligibility.